The REV7 Subunit of DNA Polymerase ζ Is Essential for Primordial Germ Cell Maintenance in the Mouse - Watanabe, Naoki (American Society for Biochemistry and Molecular Biology, 2013)
REV7 (also known as MAD2L2 and MAD2B) is involved in DNA repair, cell cycle regulation, gene expression, and carcinogenesis. In vitro studies show that REV7 interacts with several proteins and regulates their function. It has been reported that human REV7 is highly expressed in the adult testis by Northern blot analysis. However, the significance of REV7 in mammalian development has not been elucidated. Here, we present analyses of REV7-deficient (Rev7(−/−)) mice to clarify the significance of Rev7 in mouse development. In WT mice (Rev7(+/+)), Rev7 expression was ubiquitously observed in the embryo and confined to germ cells in the testes after birth. Rev7(−/−) mice exhibited growth retardation and a partial embryonic lethal phenotype. Mice that survived to adulthood were infertile in both sexes and showed germ cell aplasia in the testes and ovaries. Analyses of Rev7(−/−) embryos revealed that primordial germ cells (PGCs) were present at embryonic day 8.5 (E8.5). However, progressive loss of PGCs was observed during migration, and PGCs were absent in the genital ridges at E13.5. An increase of apoptotic cells was detected not only among PGCs but also in the forebrain of the Rev7(−/−) embryo, whereas cell proliferation was unaffected. Moreover, DNA damage accumulation and increased levels of histone methylation were detected in Rev7(−/−) embryos, and expression of Oct4 and Nanog was deregulated by REV7 deficiency at E8.5. These findings indicate that Rev7 is essential for PGC maintenance by prevention of apoptotic cell death in the mouse.